Severe brain involvement in 5q spinal muscular atrophy type 0. Issue 3 (24th July 2019) - Mendonça, Rodrigo H.; Rocha, Antônio J.; Lozano‐Arango, Andres; Diaz, Astry B.; Castiglioni, Claudia; Silva, André M. S.; Reed, Umbertina C.; Kulikowski, Leslie; Paramonov, Ida; Cuscó, Ivon; Tizzano, Eduardo F.; Zanoteli, Edmar
Abstract : Spinal muscular atrophy (SMA) type 0 is the most severe form of SMA, associated with the SMN1 gene and manifesting at birth. Most patients die in the first weeks of life. In this work, we present 3 patients with SMA type 0 who survived >1 year and presented diffuse and progressive brain abnormalities on magnetic resonance imaging, which are not usually seen in patients with SMA. Thus, severe brain involvement may likely be the full end manifestation of an already extreme SMA phenotype caused by substantial reduction of the SMN protein in the brain. ANN NEUROL 2019;86:458–462